2021
DOI: 10.1002/pc.26419
|View full text |Cite
|
Sign up to set email alerts
|

Abrasion‐resistance of UHMWPE reinforced by illite‐smectite interstratified clay and low dose radiation

Abstract: Ultra-high molecular weight polyethylene (UHMWPE)/illite-smectite interstratified clay minerals (ISIC) composites were irradiated by γ-ray in air and N 2 at 75 kGy. The abrasion-resistance of composites were studied via a ringon-ring friction tester under dry friction conditions. Compared with virgin UHMWPE, the friction coefficient and wear rate of UHMWPE filled with 0.5 wt% ISIC powders and irradiated by γ-ray in N 2 could be further reduced by near 3.1% and 88.0%, respectively. The worn surfaces of the UHMW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…5,6 Among the pool of polymers, ultrahigh molecular weight polyethylene (UHMWPE) is extensively explored for biomedical [7][8][9] and ballistic applications. [10][11][12][13][14][15][16] Owing to high tensile strength and flexibility, UHMWPE has a low melting temperature (<155 C) and is viscoelastic, thus can only be utilized in a low-temperature window. 17,18 VO 2 -based UHMWPE polymer composite was recently explored for its high-temperature mechanical strength by the split Hopkinson pressure bar test by Verma et al 19 It was shown that above 75 C, the VO 2 -based UHMWPE exhibits increased dynamic mechanical strength, because of the phase transition of VO 2 from monoclinic to tetragonal, consequently leads to an increase in elastic modulus and hardness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Among the pool of polymers, ultrahigh molecular weight polyethylene (UHMWPE) is extensively explored for biomedical [7][8][9] and ballistic applications. [10][11][12][13][14][15][16] Owing to high tensile strength and flexibility, UHMWPE has a low melting temperature (<155 C) and is viscoelastic, thus can only be utilized in a low-temperature window. 17,18 VO 2 -based UHMWPE polymer composite was recently explored for its high-temperature mechanical strength by the split Hopkinson pressure bar test by Verma et al 19 It was shown that above 75 C, the VO 2 -based UHMWPE exhibits increased dynamic mechanical strength, because of the phase transition of VO 2 from monoclinic to tetragonal, consequently leads to an increase in elastic modulus and hardness.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of polymer composites are commercially available for such uses however polymers are known to be sensitive to temperature and strain rate as they are viscoelastic in nature 5,6 . Among the pool of polymers, ultrahigh molecular weight polyethylene (UHMWPE) is extensively explored for biomedical 7–9 and ballistic applications 10–16 . Owing to high tensile strength and flexibility, UHMWPE has a low melting temperature (<155°C) and is viscoelastic, thus can only be utilized in a low‐temperature window 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is extensively applied in the development of protective armors for soldiers and other military fields. [ 12–14 ] Over the recent years, some researchers have attempted to utilize the outstanding energy absorption capacity of UHMWPE fiber for preparing FMLs with enhanced high‐velocity impact resistance. Li et al [ 15 ] compared the high‐velocity impact resistance of two kinds of FMLs prepared by carbon FRCs and UHMWPE FRCs with Ti‐6Al‐4V titanium alloy, and the results indicated that the latter had a better ballistic performance than the former in terms of ballistic limit and energy absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is extensively applied in the development of protective armors for soldiers and other military fields. [12][13][14] Over…”
mentioning
confidence: 99%